The Impact of Changes to an Electronic Admission Order Set on Prescribing and Clinical Outcomes in the Intensive Care Unit - Muniga, Ellen T.; Walroth, Todd A.; Washburn, Natalie C. (Applied Clinical Informatics, 2020)
Background Implementation of disease-specific order sets has improved compliance with standards of care for a variety of diseases. Evidence of the impact admission order sets can have on care is limited.Objective The main purpose of this article is to evaluate the impact of changes made to an electronic critical care admission order set on provider prescribing patterns and clinical outcomes.Methods A retrospective, observational before-and-after exploratory study was performed on adult patients admitted to the medical intensive care unit using the Inpatient Critical Care Admission Order Set. The primary outcome measure was the percentage change in the number of orders for scheduled acetaminophen, a histamine-2 receptor antagonist (H2RA), and lactated ringers at admission before implementation of the revised order set compared with after implementation. Secondary outcomes assessed clinical impact of changes made to the order set.Results The addition of a different dosing strategy for a medication already available on the order set (scheduled acetaminophen vs. as needed acetaminophen) had no impact on physician prescribing (0 vs. 0%, p = 1.000). The addition of a new medication class (an H2RA) to the order set significantly increased the number of patients prescribed an H2RA for stress ulcer prophylaxis (0 vs. 20%, p < 0.001). Rearranging the list of maintenance intravenous fluids to make lactated ringers the first fluid option in place of normal saline significantly decreased the number of orders for lactated ringers (17 vs. 4%, p = 0.005). The order set changes had no significant impact on clinical outcomes such as incidence of transaminitis, gastrointestinal bleed, and acute kidney injury.Conclusion Making changes to an admission order set can impact provider prescribing patterns. The type of change made to the order set, in addition to the specific medication changed, may have an effect on how influential the changes are on prescribing patterns.
Keywords: admission order set; intensive care unit; prescribing patterns; electronic health record